The Effectiveness of Nonformal Education Programs on Street Children's Self-Esteem: A Systematic Literature Review - Risma Nur Avita; Abdul Muhid (Universitas Negeri Padang, 2023)
Street children are individuals who are prone to earn a living or live along the road and often get negative stigma by the community. Street children have lives that are vulnerable to various problems, such as: sexual abuse, drug trafficking, child exploitation, etc. The phenomenon of street children is in the spotlight for the community, this is because the number of street children is increasing from time to time. There are previous studies which reveal that street children have low self-esteem. The purpose of this study is to find out and explore further about the effectiveness of out-of-school education programs to increase the self-esteem of street children. The making of this research uses a systematic literature review study method. The results obtained in the discussion show that educational programs outside of school, such as shelter homes, moral and spiritual guidance, skills training, etc. can increase self-esteem in street children.